Design and Application of Online Monitoring System for Catenary Compensation Device - Guangdong LIU; Mingli WU; Min WEI; Zhijie JIAO (机车电传动)
In order to make up for the lack of detection methods for catenary in China, a set of on-line monitoring system for catenary compensation devices was designed, realizing the functions of collecting, transmitting, storing, displaying and analyzing the b-value of the catenary compensation device. The data information was collected by the hardware detection terminal and wirelessly transmitted via GPRS. With website development, the data information was received and analyzed in real time to get the b-value and temperature fitting formula, and then predicted the change of b-value over the future time period. According to the b-value fluctuation,the contact suspension fault existing in the catenary was judged. With the testing and verification, the system has high measurement accuracy and strong stability.